Inovasi Domestik dan Redistribusi Peran dalam Keluarga Petani Kelapa Sawit: Studi Kasus Merempan Hulu, Kabupaten Siak, Provinsi Riau sebagai Model Pencegahan Stunting Berbasis Gender - Nayati, Widya; Handajani, Suzie; Noviandi, Cuk Tri; Sisparyadi, Sisparyadi; Yunita, Shielvy Nurul; Oktabi, Nouruz Zaman; Abdurrohim, Abdurrohim (Pusat Studi Wanita dan Keluarga UGM, 2025)
This study originates from the persistent issue of high stunting rates in Merempan Hulu Village, Siak District, Riau Province—an area considered economically prosperous due to palm oil cultivation and small-scale livestock farming. The research reveals that unequal gender roles within household dynamics significantly contribute to poor childcare and nutrition quality. Employing gender as structure and feminist political economy frameworks, this article examines how patriarchal norms in agrarian families can be transformed through locally embedded interventions, such as household vegetable gardening, poultry and fish raising, fermented cattle feed production, and increased paternal involvement in childcare and meal preparation. Findings indicate that men's active participation in domestic tasks not only disrupts rigid gender structures but also strengthens household food resilience and overall family well-being. The role of academics as social facilitators proves crucial in guiding agrarian families toward more collaborative and inclusive models of household management.